Personality test system for secondary school students / Mastura Alias - Alias, Mastura (2006)
Personality Test System for secondary school provides personality test through the web. Based on this system the students can answer the questions and after finish it, they can also know their score after complete the test. The score is stored in database so that they can view anytime and the counseling teacher can edit the information. The questions in test that be used in is using the personality traits questionnaires. This system used the personality traits that were introduced by Raymond Cattell. The answer of the question is calculated by using the method that was introduced by Raymond Cattell. This system is useful for students and the counseling teacher because it is easy and the students do not wait for a long time to know their score. It is because the personality test that exists is done by manually and sometimes the counseling teacher make mistake while calculate their score. It is hoped this system will provide an efficient manner the students and also for the counseling teacher.